FORMATION OF EFFECTIVE LOCAL SELF-GOVERNANCE AS A STRATEGIC DECENTRALIZATION OBJECTIVE - Bezena , I. (Pressing Problems of Public Administration, 2020)
The article examines the processes of decentralization of power in Ukraine at the regional level, which are designed to change the effectiveness of public authorities on the ground, will outline the responsibility for the content of the results of public work. As a result of structural changes, decentralization of public authority should positively change the socio-economic situation and strategies for the development of new organizational measures in improving the situation in the region, and will form a new vision for an effective strategy for its sustainable development.It analyzes the state of work at the regional level in various spheres of community policy and activity, from landscaping, solving problems with housing and communal services to the work of social objects and overcoming systemic problems in the territory. Some concepts of local authorities, their independence and responsibility for the efficiency of forming the revenue and expenditure part of the budgets, realization of the possibility of attracting internal and external investments to solve the problems of the territory are outlined. The author of the research proposes to determine the criteria for indexing the level of territorial development strategies, the effectiveness of regional and local authorities and their officials, monitoring the implementation of infrastructure projects aimed at reconstruction and energy-saving housing and communal funds, the formation of an effective budget for the development of the territory, etc. At the same time, the author notes a number of systemic problems that are sensitive and in need of resolution: formation of financial self-sufficiency of territories; development of local crafts aimed at employment of citizens; support effectiveness of small and medium-sized businesses; civic activity of residents; a new model of community social sphere structure, etc. Democratization and decentralization of activities of public authorities outlined the legal and practical problems in the professional competence and content of officials: the ability to constantly communicate on aspects of community activity; analytical skills and practices; citizen participation in decision-making processes; sustainable community development strategies.